Effect of Cyclic Heat Treatment on Microstructure and Mechanical Properties of AA 6061-T6 Aluminum Alloy - Mahmood, Najmuldeen Yousif; Zainulabdeen, Ahmed Ameed; Mohmmed, Jabbar Hussein; Oun, Hasanain Abd (Al-Nahrain Journal for Engineering Sciences, 2020)
The effects of the repeated solution heat treatment on hardness, tensile strength and microstructure of aluminum were investigated. For this purpose, an alloy of AA6061-T6 was undergo to cyclic solution heat treatment process which is composed of repeated period (10 min) held at 520 °C for 1, 4, 8 and 12 cycles. The hardness was tested for five aging times (as quenching, one week, three weeks, one month and five months) to all cycles (1, 4, 8 and 12) firstly and it is found that the hardness of five months as aging time for all cycles has the best results (90Hv) as compared with others (as quenching, one week, three weeks, and one month), so it was adopted for all cycles to implement the tensile test and the microstructure. Hardness results were improved to Vickers hardness of (90Hv) with increasing of cycles up to 8 cycles then decreasing after that to (45Hv). Tensile results were showed an increment (34%) also for the same group of 8 cycles compared with (17%) and (9%) for 4 and 12 cycles, respectively. Microstructure is revealed that whenever cycles are increased, the precipitate phase in alloy is increased also, thus, it is improved the hardness and tensile strength.